Serological survey of leptospirosis in horses with historical displacement through different geographic regions in Brazil - Bello de Vasconcelos, Tassia Cristina; de Castro, Marina Pinheiro; da Silva, Daniela Barbosa; Barros, Renata Simões; de Almeida, Adilson Benedito; Mendes Júnior, Artur Augusto Velho; Langoni, Helio; Figueiredo, Fabiano Borges (Medicina Veterinária, 2023)
Leptospirosis has a worldwide occurrence and shows higher incidence in tropical areas. Equines can present several serovars according to geographic region and it is important to analyze the possible contribution of animal displacement on the Leptospira spp. strains occurrence. This research aimed to conduct a serological investigation in an equine regiment belonging to the Brazilian Army Guard Cavalry, resident in an urban area of Rio de Janeiro municipality, but with a history of displacement between different regions in Brazil. A microscopic agglutination test was performed in a serum bank of 197 horses using 29 Leptospira spp. strains. The test showed 94.92% positivity, with 89.84% of the animals presenting a positive result for two or more serovars. Higher titers (?1:400) could be detected in 57.22% of horses for at least one serovar, whereas seropositivity for more than one bacterial type occurred mostly at lower titers (<1:400). All animals were clinically healthy. The occurrence of serogroup Icterohaemorraghiae in urban areas was confirmed; however, equine serovars Bratislava and Australis presented low frequencies. The serovars Hardjo, Wolffi, and Canicola were detected and indicated the presence of ruminants and dogs as typical reservoirs in proximity to the equines. It is suggested that travel history has contributed to the high frequency found and possible greater contact with different types of Leptospira spp. Therefore, veterinarians should consider the history of geographic displacement and other animal species’ coexistence with horses when conducting their clinical investigation.